Functional impacts of 5-hydroxymethylcytosine, 5-formylcytosine, and 5-carboxycytosine at a single hemi-modified CpG dinucleotide in a gene promoter. Issue 19 (17th August 2017) - Kitsera, Nataliya; Allgayer, Julia; Parsa, Edris; Geier, Nadine; Rossa, Martin; Carell, Thomas; Khobta, Andriy
Abstract: Enzymatic oxidation of 5-methylcytosine (5-mC) in the CpG dinucleotides to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine (5-fC) and 5-carboxycytosine (5-caC) has central role in the process of active DNA demethylation and epigenetic reprogramming in mammals. However, it is not known whether the 5-mC oxidation products have autonomous epigenetic or regulatory functions in the genome. We used an artificial upstream promoter constituted of one cAMP response element (CRE) to measure the impact of 5-mC in a hemi-methylated CpG on the promoter activity and further explored the consequences of 5-hmC, 5-fC, and 5-caC in the same system. All modifications induced mild impairment of the CREB transcription factor binding to the consensus 5′-TGACGTCA-3′ CRE sequence. The decrease of the gene expression by 5-mC or 5-hmC was proportional to the impairment of CREB binding and had a steady character over at least 48 h. In contrast, promoters containing single 5-fC or 5-caC underwent further progressive loss of activity, up to an almost complete repression. This decline was dependent on the thymine-DNA glycosylase (TDG). The results thus indicate that 5-fC and 5-caC can provide a signal for perpetuation and enhancement of the repressed transcriptional state by a mechanism that requires base excision repair.